Poptacular: Factors that Influence the Popularity of Funko Pops Among Malaysian Toy Collectors - Adi Bunyamin, Zamzamin (Universiti Malaysia Sarawak, 2022)
Toys such as action figures, robots and dolls are always usually associated as kid’s stuffs. The rather big rise in revenue in the toy industry is not only due to toys are being bought for children but recent studies however show that it is not unheard off for adults to buy toys specifically for themselves and these adults are known as ‘kidults’. Mostly represented by the millennial generation, the act of collecting toys shows their intimate passion with pop culture, reminiscing nostalgic childhood experiences and as a stress reliever. With many adults buying toys for themselves and their children, toy sales have increased exponentially and had bring about billions of dollars and creating a great impact on the economy. Many of these toys are very toyetic in nature as well as commercially commoditoys. Recent favourite toy collectibles, the Funko Pop, is a very popular item among Malaysian toy collectors. The popularity of Funko Pops among local collectors is on the rise especially with the drop in value of the Malaysian Ringgit, where prices of toys, especially premium collectibles have gone up extremely. Malaysian collectors were forced to look for substitutes while still being able to appreciate and support their favourite pop culture franchise. The purpose of this study was to find out what were the main factors contributing to the popularity of Funko Pops among local collectors by using the exploratory factor analysis. It is also to test the hypothesis regarding design and nostalgia (which where based on studies of consumers purchasing intent), by using the multiple regression analysis. The sampling of the population chosen was a local Funko community on facebook which has a great number of members and likert scale questionnaire was shared. Upon conducting the data analysis, four factors were formed with both hypotheses accepted. Although there are a few other factors that also influence Malaysians to buy Funko Pops, design and nostalgia play an important role for local toy collectors. These findings will hopefully be able to help local toy creators to further understand what factors should be focused on when developing their own toys. This in the future could help generate a huge impact on Malaysia’s economy through the sales of locally made toys, as in the case of many developed countries, such as the United States where Funko Pops were conceived. Keywords: Funko Pop, toy collectibles, kidults, toy collectors